Attitudes of Bangkok Office of the Narcotics Control Board Officers Toward the Policy of “Drug Users as Patients” and its Influence on Work Performance - Reansri, Ponsawan (Rajapark Journal, 2026)
This research aimed to (1) examine the attitudes of officers at the Bangkok Office of the Narcotics Control Board toward the implementation of the “Drug Users as Patients” policy; (2) investigate the level of work performance under this policy; and (3) explore problems, obstacles, and opinions regarding its practical implementation. The study employed a quantitative survey research design. The sample consisted of 54 officers selected using simple random sampling. A structured questionnaire was used as the data collection instrument. Data were analyzed using descriptive statistics (frequencies, percentages, means, and standard deviations) and inferential statistics, including t-tests, one-way ANOVAs, and multiple linear regression. Content analysis was also conducted for open-ended responses. The findings revealed that the cognitive component had a positive and statistically significant effect on work performance (Beta = 0.354, p = 0.013), and the behavioral component also demonstrated a positive and statistically significant effect at the 0.05 level (Beta = 0.471, p = 0.005). In contrast, the policy and affective components did not show statistically significant effects. Furthermore, officers reflected that the policy remains challenging to implement in practice due to limitations in rehabilitation facilities, insufficient public communication, and persistent social stigma toward drug users, which hinder successful social reintegration. Therefore, enhancing officers’ knowledge and behavioral attitudes, as well as strengthening operational support systems and interagency collaboration, is essential to improving the effectiveness and sustainability of the Policy Component.